2018
DOI: 10.1101/506188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Toolkit for Rapid Modular Construction of Biological Circuits in Mammalian Cells

Abstract: The ability to rapidly assemble and prototype cellular circuits is vital for biological research and its applications in biotechnology and medicine. Current methods that permit the assembly of DNA circuits in mammalian cells are laborious, slow, expensive and mostly not permissive of rapid prototyping of constructs. Here we present the Mammalian ToolKit (MTK), a Golden Gate-based cloning toolkit for fast, reproducible and versatile assembly of large DNA vectors and their implementation in mammalian models. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…researchers have devoted significant time, effort, and resources to improving the outcomes of mammalian cell transgenesis experiments. Much of this effort has been directed at improved vector design, resulting in the identification of many cis-acting features that affect transgene expression, including transcriptional regulatory regions (6)(7)(8)(9)(10), mRNA polyadenylation (pAn) sites (11), introns (12), mRNA export and/or translation signals (e.g. the Woodchuck Hepatitis Virus (WHP) posttranscriptional regulatory element (WPRE) ( 13)), and cis-acting inhibitors of gene silencing (10,14).…”
Section: Manymentioning
confidence: 99%
See 1 more Smart Citation
“…researchers have devoted significant time, effort, and resources to improving the outcomes of mammalian cell transgenesis experiments. Much of this effort has been directed at improved vector design, resulting in the identification of many cis-acting features that affect transgene expression, including transcriptional regulatory regions (6)(7)(8)(9)(10), mRNA polyadenylation (pAn) sites (11), introns (12), mRNA export and/or translation signals (e.g. the Woodchuck Hepatitis Virus (WHP) posttranscriptional regulatory element (WPRE) ( 13)), and cis-acting inhibitors of gene silencing (10,14).…”
Section: Manymentioning
confidence: 99%
“…Much of this effort has been directed at improved vector design, resulting in the identification of many cis-acting features that affect transgene expression, including transcriptional regulatory regions (6)(7)(8)(9)(10), mRNA polyadenylation (pAn) sites (11), introns (12), mRNA export and/or translation signals (e.g. the Woodchuck Hepatitis Virus (WHP) posttranscriptional regulatory element (WPRE) ( 13)), and cis-acting inhibitors of gene silencing (10,14). Other studies have revealed that transgene expression can be improved by eliminating or reducing bacterial or viral sequences that may induce transgene silencing (15,16), such as by use of DNA mini-circles (17) or DNA transposons (e.g.…”
Section: Manymentioning
confidence: 99%
“…A computational campaign was conducted to identify short protein sequences that were able to bind the Spike protein 23 , and we incorporated the lead candidate from this screen (LCB1) into our initial antigen sensor panel ( Figure 1A ). Using our Mammalian Cloning Toolkit 31 , we rapidly constructed multiple SynNotch variants with these different extracellular sensors for Spike.…”
Section: Resultsmentioning
confidence: 99%
“…The output circuit, pHR_Gal4UASpyb-TATA_tBFP_pGK_mCitrine, was a generous gift from Dr. Kole Roybal. All other plasmids were constructed using the Mammalian Toolkit (MTK) 31 , a hierarchical DNA assembly method based on Golden-Gate (GG) cloning 56 . New binding domains were domesticated into the MTK by ordering primers or gBlocks from IDT that contained the desired coding sequence with all BsaI and BsmBI restriction sites replaced with synonymous mutations and overhangs for MTK Part 3as, then ligated into the MTK part entry vector using a BsmBI GG reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Lentivirus particles were generated as described previously 47 . In short, LX-HEK293T cells were seeded at approximately 50% confluency in a 6-well plate, and the following day were transfected with lentiviral vector of interest alongside packaging plasmids (pCMV-dR8.91 and pCMV-VSV-G) using Lipofectamine 3000 (Thermo) according to manufacturer's instructions.…”
Section: Lentiviral Productionmentioning
confidence: 99%